Shear Behavior of Random Rockfill in Dam Construction via Large-Scale In-Situ Testing - Sahadewa, Andhika; Hakim, Abi M.; Setyawan, Haris E.; Kamaruddin, Samira A.; Krisnanto, Sugeng (Civil Engineering Journal, 2025)
Dam construction commonly demands a massive amount of random material. This material offers practical material collection, minimum environmental impact, and economical cost. Unfortunately, shear strength assessment of random material is difficult because of large particle presence. Regular laboratory tests cannot accommodate these large particles. Misevaluation of random material shear strength may induce disastrous collapse. A large-scale direct shear apparatus, with a 70 cm by 70 cm shear plane, was developed and proposed for testing random fill material in-situ. This manuscript presents an experimental study using this device in Rukoh Dam construction, Indonesia. Test results captured variations between normal stress and shear stress to determine shear strength parameter models. Volume changes during shearing were also observed. Random materials in Rukoh Dam could be categorized as random rock. This study was also compared to other relevant rockfill studies. The proposed method offers an impressive approach for assessing and verifying the shear strength of compacted random material as well as compaction quality on site. It can be used to decide if the ongoing design and compaction method have to be modified or continued. Since the proposed direct shear test is reliable, fast, simple, and inexpensive, it is strongly recommended for dam construction.